2016
DOI: 10.5465/amle.2014.0104
|View full text |Cite
|
Sign up to set email alerts
|

“What’s Going On?” Developing Reflexivity in the Management Classroom: From Surface to Deep Learning and Everything in Between

Abstract: 'What's going on?' Within the context of our critically-informed teaching practice, we see moments of deep learning and reflexivity in classroom discussions and assessments. Yet, these moments of criticality are interspersed with surface learning and reflection. We draw on dichotomous, linear developmental, and messy explanations of learning processes to empirically explore the learning journeys of 20 international Chinese and 42 domestic New Zealand students. We find contradictions within our own data, and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 47 publications
0
31
0
Order By: Relevance
“…Our analysis followed well-established procedures for inductively building theory from qualitative data (Corbin & Strauss, 2008;Denzin & Lincoln, 2000), along with guidelines for coding and working with student reflection data as suggested by other authors (Dyer & Hurd, 2016). To improve the trustworthiness and interpretive rigor of the data analysis process (Denzin, 1989), the coding process was led by the first two authors and proceeded in two stages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our analysis followed well-established procedures for inductively building theory from qualitative data (Corbin & Strauss, 2008;Denzin & Lincoln, 2000), along with guidelines for coding and working with student reflection data as suggested by other authors (Dyer & Hurd, 2016). To improve the trustworthiness and interpretive rigor of the data analysis process (Denzin, 1989), the coding process was led by the first two authors and proceeded in two stages.…”
Section: Discussionmentioning
confidence: 99%
“…Second, prior empirical studies in management education have shown that students' written reflections completed as part of course assessment have 'interpretive validity' (Maxwell, 1992) as meaningful accounts of student learning, which makes them suitable for use as 'research instruments' for investigating differences in student understanding (Carson & Fisher, 2006;Dyer & Hurd, 2016;Lovelace et al, 2016). Prior research also shows that students vary in the depth of reflection, as displayed in writing tasks (Dyer & Hurd, 2016;Dyment & O'Connell, 2011). Since our research purpose relies on exploring differences in student understanding of EBMgt, variations in the depth of students' written reflections are theoretically salient.…”
Section: Research Instrument and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data analysis was guided by our research question as well as guidelines for working with student reflection texts suggested by other authors (Dyer & Hurd, 2016). We began by using the literature on threshold concepts as a sensitizing framework (Corbin & Strauss, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…For our members, in common with the authors of the Journal of Management Education, the sites of inquiry are varied, ranging anything from the traditional classroom and lecture theatre (cf. Durant, Carlon andDowns 2016, Dyer andHurd 2016), to organizational setting where researcher-practitioner working spaces generate insights through action-oriented, collaborative research (cf. Scaratti 2017, Radaelli et al 2014).…”
Section: Management Education In Turbulent Times Introductionmentioning
confidence: 99%